A 10-Year Retrospective Analysis of 64 Cases of Cystic Lesions of the Oral and Maxillofacial Region in a Nigerian Tertiary Hospital - Fomete, Benjamin (Oman Med J, 2016)
OBJECTIVES: Orofacial cysts are broadly divided into odontogenic and nonodontogenic types, epithelial or non-epithelial, and developmental or inflammatory in origin. The odontogenic cyst is an osseous-destructive lesion that most commonly affects the jaw. It is formed by activation of odontogenic cell rests entrapped within the bone or gingival tissue of the jaws, such as the epithelial remains of Malassez, the dental lamina (cell rests of Serres), or the enamel organ. METHODS: We performed a retrospective study of all histologically diagnosed cysts of the orofacial region seen at the Maxillofacial clinic of the Ahmadu Bello University Teaching Hospital, Nigeria, between January 2003 and December 2012. RESULTS: Over the 10-year study period, 64 cases of cystic lesions of the orofacial region were seen in 1162 pathological specimens, representing 5.5%. Of these, there were 35 (54.7%) lesions in males and 29 (45.3%) in females giving a M:F ratio of 1.2:1. The age of the patients ranged from 4–64 years old (mean = 26.3 years). Dentigerous cyst (n = 21; 32.8%) was the most predominant lesion followed by periodontal (n = 12; 18.8%) and radicular cysts (n = 10; 15.6%). CONCLUSIONS: Cysts of the orofacial region are common in this environment and like previous studies from Nigeria odontogenic cysts are not uncommon, the most predominant being dentigerous cysts.